Design and fabrication of microstrip patch antenna using conformal substrates - Athirah binti Mohd Ramly (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Three dimension (3D) printing is one of the additive manufacturing technology that has gain popularity for time saving and complex design. This technology increases a degree of flexibility for potential 3D radio frequency (RF) applications such as wearable and conformal antennas. This dissertation demonstrates a circular patch antenna fabricated on 3D printed Acrylonitrile Butadiene Styrene (ABS) filament. The main reason of using a 3D printer is that it is accurate, easy to fabricate of a complex geometry and the ability to create new antennas that cannot be made using conventional fabrication techniques. The ABS material has a tangent loss of 0.0051 and the relative permittivity is 2.74. The thickness of the substrate is 1.25 mm. The simulation has been performed using Computer Simulation Technology (CST). Apart from that, another material is to be used is Polydimethylsiloxane (PDMS). The PDMS has the tangent loss of 0.04 and 2.68 for the relative permittivity. The thickness of the PDMS is 2mm. The return loss from simulation software is in good match with measurement which is 12.5dB at 2.44GHz for ABS whereas for PDMS, the measurement is matched with simulation with the values of 38.4dB and 42.2dB. Hence, from the results obtained, the ABS and PDMS could be used as a substrate for an antenna. The flexibility of the substrates are the key element in producing a conformal antenna substrates and it could be used as a wearable antenna in many applications such as in medical application.